2019
DOI: 10.1038/s41598-019-41894-8
|View full text |Cite
|
Sign up to set email alerts
|

Azoreductase activity of dye-decolorizing bacteria isolated from the human gut microbiota

Abstract: The gut microbiota enriches the human gene pool and contributes to xenobiotic metabolism. Microbial azoreductases modulate the reduction of azo-bonds, activating produgs and azo polymer-coated dosage forms, or degrading food additives. Here, we aimed to screen the healthy human gut microbiota for food colorant-reducing activity and to characterize factors modulating it. Four representative isolates from screened fecal samples were identified as E. coli (AZO-Ec), E. faecalis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(39 citation statements)
references
References 64 publications
0
38
0
1
Order By: Relevance
“…The performance of different microorganisms on the decolorization of the mixture of azo dyes was previously studied in a few reports 27 29 . While evaluating the decolorization of the mixtures of azo dyes by the S. halophilus strain SSA1575, it was observed that this halotolerant yeast strain was effectively decolorized mixture of azo dyes.…”
Section: Resultsmentioning
confidence: 99%
“…The performance of different microorganisms on the decolorization of the mixture of azo dyes was previously studied in a few reports 27 29 . While evaluating the decolorization of the mixtures of azo dyes by the S. halophilus strain SSA1575, it was observed that this halotolerant yeast strain was effectively decolorized mixture of azo dyes.…”
Section: Resultsmentioning
confidence: 99%
“…To understand the decolorization and degradation mechanism of DMS2, enzyme activity of azoreductase, laccase, NADH-DCIP, lignin peroxidase and tyrosinase were studied (Kurade et al, 2016;Liu, 2017). Azo-bonds of the dye were broken down via azoreductase enzymes and generate aromatic amines (Singh et al, 2015;Zahran et al, 2019). Consequently, these amines undergo further cleavage by the use of different oxidative enzymes, which finally enter into the central metabolic pathways.…”
Section: Assessing the Catabolic Efficiency Of Dms2mentioning
confidence: 99%
“…Among azo-reducing bacteria are Clostridium, Pseudomonas, Bacillus, Geobacillus, Lysinibacillus, Enterococcus, Eubacterium, and Escherichia (Misal and Gawai, 2018). Escherichia coli, Enterococcus faecalis, Enterococcus avium, and Bacillus cereus/thuriengensis have been recently isolated from human stool samples with variable azoreduction rates (Zahran et al, 2019).…”
Section: Environmental Chemicals and Pollutantsmentioning
confidence: 99%